To have and have not - Hemingway, Ernest, 1899-1961. (New York : Simon & Schuster, 1996)
Harry Morgan, seeking to earn a living for himself and his family, turns to rum-running between Cuba and Key West during the depression of the 1930s.
Wilson's Fiction.
Young Adult
Keywords: Smuggling -- Caribbean Area -- Fiction; Adventure fiction; Smuggling -- Fiction; Caribbean Area -- Fiction; Caribbean Area -- Fiction